The Influence of Macroeconomic Factors on The Indonesia’s Sovereign Credit Default Swap (SCDS) Spread - Winanda Epriyanti; Wendy Wendy (International Journal of Economics Development Research (IJEDR), 2024)
SCDS spread is an indicator that can be used to determine investment risk in a country. This research aims to determine the influence of macroeconomic factors, namely the inflation rate, GDP, IDX Composite Index, exchange rate, and BI reference interest rate on the movement of Indonesia's SCDS spread with a five-year tenor. The data analysis method uses a multiple linear regression model. The sample period that will be used in this research uses monthly time series data, namely 168 months (January 2010 to December 2023). The research results show that the inflation rate and exchange rate have a significant and positive effect on Indonesia's SCDS spread. Meanwhile, GDP and IDX Composite Index have a significant and negative effect on Indonesia's SCDS spread. The GDP variable is the macroeconomic factor that has the most influence on the movement of Indonesia's SCDS spread with a regression coefficient of -1.73. The independent variable used in this research is able to explain its influence on the dependent variable (Indonesia’s SCDS spread ) by 66.65% and the remaining 33.35% is explained by other variables that were not included in the research.